A thin clothe coated architecture of ZnIn2S4/H2Ta2O6 for enhanced photocatalytic hydrogen production. (11th November 2021) - Ma, Yuxuan; He, Dan; Wang, Xiaojing; Fu, Yuan
Abstract: Focused on energy and environment issues, in present investigation, an economical and eco-friendly photocatalyst for hydrogen evolution in water splitting reaction has been designed and fabricated. The characteristics by XRD, TEM, XPS and AFM confirmed that an octahedral H2 Ta2 O6 is uniformly capsuled by ZnIn2 S4 thin clothes to form a package ZnIn2 S4 /H2 Ta2 O6 heterojunction. The assembled ZnIn2 S4 /H2 Ta2 O6 exhibits superior hydrogen generated performance with a value of 3217.31 μmol g −1 h −1 under simulated sunlight irradiation, without obvious deactivation in five consecutive cycles. The enhanced activity and reusability are mainly attributed to ultrathin clothe-like shell, the well-matched band structure and a large tight contact interface in the package type construction, which can promote redox ability, extend light harvesting range and boost charge separation efficiency. The present study proposes a new design idea to assemble a highly efficient and durable photocatalyst for solar hydrogen generation by splitting water. Graphical abstract: Image 1 Highlights: A package ZnIn2 S4 /H2 Ta2 O6 heterojunction was prepared by one-step synthetic method. The enhanced activity is due to the formation of tightly connected interface. Large surface area and modified electronic structure contribute to the activity. The ZnIn2 S4 /H2 Ta2 O6 showed well reusability during 30 h of stability test.